Supine Frequent Ventricular Extrasystoles in a Pregnant Woman without Structural Heart Disease. (25th August 2016) - Ferreira, Natália Stela Sandes; Barros, Tatiana La Croix; Gismondi, Ronaldo Altenburg
Abstract : Arrhythmias are the most common cardiac complication during gestational period and may occur in women with or without known structural heart disease. Premature extra beats and sustained tachyarrhythmias are the most common arrhythmias in pregnancy. Symptomatic episodes occur in 20–44% of pregnant women, usually as palpitations, dizziness, or syncope. We searched on Pubmed for ventricular premature complexes (VPC) in pregnant women and found no case reporting increased incidence of this arrhythmia while supine. The aim of this study is to report a case of a pregnant woman without previous structural heart disease that presented a great number of VPC when supine. The arrhythmogenesis increase during pregnancy is multifactorial. In the reported case, we believe that augmented venous return was the most important pathophysiologic process. When the patient changes to left lateral decubitus, there could be a sudden release of the inferior vena cava, causing an abrupt augmentation of venous return to the right heart chambers and increasing the risk of arrhythmias. Obstetricians and primary care physicians should be aware of palpitations and related patient complains while they are asleep or supine.